2021
DOI: 10.1007/s12311-021-01264-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Neural Transmission after Cerebellar Fastigial Nucleus Lesions in Juvenile Rats

Abstract: Structural and functional abnormalities in the cerebellar midline region, including the fastigial nucleus, have been reported in neuropsychiatric disorders, also comprising the cerebellar cognitive affecting syndrome. In rats, early fastigial lesions reduce social interaction during development and lead to cognitive and emotional deficits in adults, accompanied by compromised neuronal network activity. Since epigenetic mechanisms are implicated in the etiology of neuropsychiatric disorders, we investigated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…One study using a mutant mouse line with Purkinje cell death reported that mutants spent more time in the open arms of the elevated plus maze, suggesting an anti-anxiety phenotype (Hilber et al, 2004 ). Bilateral lesion of the MN in juvenile rats was shown to alter anxiety in adulthood although it was not clear whether the anxiety was enhanced or decreased (Helgers et al, 2020 ), accompanied by enhancement of local field coherence between the medial prefrontal cortex and the sensorimotor cortex (Helgers et al, 2020 ) and epigenetic dysregulation of the GABAergic system in the nucleus accumbens and the oxytocin system in the prefrontal cortex (Helgers et al, 2021 ). Cerebellar manipulation can also change fear responses, an affective component of pain.…”
Section: Cerebellar Manipulation Modulates Pain In Animalsmentioning
confidence: 99%
“…One study using a mutant mouse line with Purkinje cell death reported that mutants spent more time in the open arms of the elevated plus maze, suggesting an anti-anxiety phenotype (Hilber et al, 2004 ). Bilateral lesion of the MN in juvenile rats was shown to alter anxiety in adulthood although it was not clear whether the anxiety was enhanced or decreased (Helgers et al, 2020 ), accompanied by enhancement of local field coherence between the medial prefrontal cortex and the sensorimotor cortex (Helgers et al, 2020 ) and epigenetic dysregulation of the GABAergic system in the nucleus accumbens and the oxytocin system in the prefrontal cortex (Helgers et al, 2021 ). Cerebellar manipulation can also change fear responses, an affective component of pain.…”
Section: Cerebellar Manipulation Modulates Pain In Animalsmentioning
confidence: 99%
“…Knowing that a variety of manipulations of afferent signaling to the cerebellar cortex, and disruption of cerebellar cortical function both lead to dystonia, we sought to devise a paradigm that would allow for the reliable induction of highly focal lesions to test whether disruption of cerebellar efferent signaling would also produce dystonia. Previous groups have used monopolar electrodes to induce lesions of the fastigial (medial) nucleus in rats[1, 33, 34]. Therefore, using tungsten electrodes, we sought to deliver a charge of 1600 mA at 50 Hz using a pulse generator attached to the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, acute lesioning of the cerebellar outflow tract leads to a constellation of symptoms termed the cerebellar cognitive affective syndrome, the severity of which occurs in direct proportion to the percent damage to the tract bilaterally[3, 35]. In rats, lesioning of the medial (fastigial) cerebellar nuclei has also been associated with a constellation of behavioral deficits[1, 33, 34]. In mice, the sequelae of lesioning of the cerebellar outflow tracts have not been examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations